2013
DOI: 10.2478/pjvs-2013-0052
|View full text |Cite
|
Sign up to set email alerts
|

The serum protein electrophoretic pattern and acute phase protein concentrations in calves with chronic respiratory diseases

Abstract: The aim of this study was to evaluate the serum protein electrophoretic pattern and the concentrations of acute phase proteins (haptoglobin, serum amyloid A, and fibrinogen) in 28 calves with clinical signs of chronic respiratory diseases and 36 healthy calves as a control group. In sick calves we found significantly higher serum concentrations of total proteins (P<0.001), lower concentrations of albumin (P<0.001) and marked shift in the concentrations of the most of protein fractions with significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…22 However, an increase in Hp was also observed to precede abscess formation in goats experimentally infected with Corynebacterium pseudotuberculosis , 21 whereas the SAA level remained unchanged. A significantly higher proportion of cattle with acute inflammation were found to have higher values of SAA and Hp than those with chronic inflammation, 17,20 but in one study 32 both APPs were significantly elevated in calves with chronic respiratory disease. Obviously, a prospective study is warranted to determine changes of APPs in the course of chronic SRLV infection.…”
Section: Discussionmentioning
confidence: 84%
“…22 However, an increase in Hp was also observed to precede abscess formation in goats experimentally infected with Corynebacterium pseudotuberculosis , 21 whereas the SAA level remained unchanged. A significantly higher proportion of cattle with acute inflammation were found to have higher values of SAA and Hp than those with chronic inflammation, 17,20 but in one study 32 both APPs were significantly elevated in calves with chronic respiratory disease. Obviously, a prospective study is warranted to determine changes of APPs in the course of chronic SRLV infection.…”
Section: Discussionmentioning
confidence: 84%
“…Since many acute phase proteins migrate in the α region, the concentrations of α 1 -and α 2 -globulins may be elevated in acute, as well as chronic inflammatory diseases as a result of the activation of the host inflammatory responses (O'Connell et al 2005). Increased α-globulins (predominantly α 1 -globulins) were found in sheep naturally infected with Babesia ovis, as well as in calves affected by respiratory diseases (Apaydin and Dede 2010;Tothova et al 2013b). The α 2 -globulin fraction typically increases in patients with nephrotic syndrome as a result of the increased synthesis of α 2 -macroglobulin that migrates in this fraction.…”
Section: Globulinsmentioning
confidence: 99%
“…In this study, diseased sheep had significantly lower albumin, and higher α 1 -and γ-globulin concentrations. Recently, Tothova et al (2013b) evaluated the effect of chronic bronchopneumonia on the serum protein pattern in calves. These authors found significantly higher concentrations of α 1 -, β 2 -and γ-globulins in the affected animals compared with healthy ones.…”
Section: The Usefulness Of Serum Protein Electrophoresis In Clinical mentioning
confidence: 99%
“…During the acute phase response, the requirement for amino acids increases for synthesis of acute phase proteins such as haptoglobins which plays important role in alterations in hepatic protein synthesis leading to elevation in globulin levels, thus the production of other proteins such as albumin will be curtailed. The acute phase reaction leads to hyperglobulinemia, hyperproteinemia, hypoalbuminemia and lower albuminglobulin ratio (Tothova et al 2013).…”
Section: Discussionmentioning
confidence: 99%